Trigonometric and linear widths for the classes of periodic multivariable functions - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish the exact-order estimates for the trigonometric widths of Nikol’skii – Besov B^r_∞ ,θ and Sobolev W^r_∞, α classes of periodic multivariable functions in the space L_q, 1 < q < ∞. The behavior of the linear widths of Nikol’skii – Besov B^r_∞ ,θ classes in the space L_q is investigated for certain relations between the parameters p and q.